Implementation of Pancasila Values in Students in Everyday Life - Revi Afifah; Nanda Ratri Fadilah (Eastasouth Institute, 2023)
By applying the values of Pancasila in everyday life, students will be able to face various problems that will occur in the future. Pancasila values can be implemented through practice, habituation, exemplary, and environmental conditioning. It can also be applied through inculcation (instilling values), modeling (ideal), facilitation (facilitation), and skill-building (skills development) approaches. The results section will briefly discuss the implementation of Pancasila in each Precept. The purpose of writing this article is to implement Pancasila values for students in everyday life. In analyzing the data, it was carried out using descriptive analysis with the library research method, namely collecting research data on theories related to the problems discussed in this study; the source of the data obtained as a reference to support this research comes from several relevant articles and journals. And they are aligned with research related to the implementation of Pancasila values. There are so many reasons why students have been unable to implement Pancasila values in life—some of them the flow of globalization, the use of technology, and many more. Globalization occurs without stopping, extending to various sectors of life, and giving rise to new challenges and problems, including for students. Pancasila values also fade; the noble values of Indonesian society no longer reflect what has been contained in Pancasila. The impact of this research is that the writer can understand and implement Pancasila values for students, and readers can do it in everyday life so that the noble values of Pancasila return to the nation's young generation.